Association of neighborhood physical activity opportunities with incident cardiovascular disease in the Cardiovascular Health Study. (July 2021) - Garg, Parveen K.; Platt, Jonathan M.; Hirsch, Jana A.; Hurvitz, Philip; Rundle, Andrew; Biggs, Mary Lou; Psaty, Bruce M.; Moore, Kari; Lovasi, Gina S.
Abstract: We determined associations of cumulative exposures to neighborhood physical activity opportunities with risk of incident cardiovascular disease (CVD). We included 3595 participants from the Cardiovascular Health Study recruited between 1989 and 1993 (mean age = 73; 60% women; 11% black). Neighborhood environment measures were calculated using Geographic Information Systems (GIS) and annual information from the National Establishment Time Series database, including the density of (1) walking destinations and (2) physical activity/recreational facilities in a 1- and 5-km radius around the respondent's home. Incident CVD was defined as the development of myocardial infarction, stroke, or cardiovascular death and associations with time to incident CVD were estimated using Cox proportional hazards models. A total of 1986 incident CVD cases occurred over a median follow-up of 11.2 years. After adjusting for baseline and time-varying individual and neighborhood-level confounding, a one standard deviation increase in walking destinations and physical activity/recreational facilities within 5 km of home was associated with a respective 7% (95% confidence interval (CI) = 0.87–0.99) and 12% (95% CI = 0.73–1.0) decreased risk of incident CVD. No significant associations were noted within a 1-km radius. Efforts to improve the availability of physical activity resources in neighborhoods may be an important strategy for lowering CVD. Highlights: We examined the association of neighborhood physical activity opportunities and cardiovascular disease risk in older adults. Neighborhood measures were calculated using Geographic Information Systems and National Establishment Time Series database. Higher number of walking destinations within 5 km of home was associated with a reduced CVD risk. Higher number of physical activity/recreational facilities within 5 km of home was also associated with a reduced CVD risk.